LINGUOCULTURAL STUDY OF THE TERM “FOOD” IN ENGLISH AND UZBEK LANGUAGES - Vakhobova , Dilnavo Farkhod kizi; Akhmadjonova , Shakhnoza (Innovative Development in Educational Activities, 2023)
Proverbs are considered the most ancient genre of folk art, they reflect the past, cultural heritage and values of the people. At the moment, in-depth research is being conducted on proverbs in linguistics, and as a result of such research, scientists are opening new aspects of linguistics. This article of ours is one of those researches, in which, through a comparative study of Uzbek and English proverbs, we not only express the degree to which the cultural and national customs of both peoples are reflected in the language, but also the similarities in the national mentality of the peoples. and aimed at revealing the differences. In order to study this issue, we analyzed the proverbs related to the theme of "food" in English and Uzbek folk proverbs from a linguistic and cultural point of view.